Effect of Nature-based physical activity on post-traumatic growth among Healthcare providers with post-traumatic Stress: Protocol for a randomized controlled trial. - Noushad , Shamoon; Ansari, Basit; Ahmed , Sadaf; Saleem, Yusra (International Journal of Endorsing Health Science Research, 2020)
Background: In the aftermath of trauma, post-traumatic growth is demarcated as a positive change and traumatic stress as a negative change, which further leads to PTSD. Previous studies have also indicated that both constructs can co-exist. Detailed descriptions of post-traumatic stress reactions are available in the literature, but the psychophysiological phenomenon of post-traumatic growth is still unclear. Studies have shown that the restorative effects of nature-based therapy have been accounted for a reduction in stress and increase positive affect. The purpose of designing this randomized control trial is to observe nature-based walk on post-traumatic growth and Psychophysiological alterations associated with it. Methodology: This study is designed to examine recreational exposure to the natural environment for the promotion of post-traumatic growth among health care providers with traumatic stress. In addition, to assess whether post-traumatic growth is associated with psychophysiological alterations, i.e. Cortisol, C-Reactive Protein, Interleukin-6, Brain-Derived Neurotropic Factor and Heart Rate Variability. At baseline, the participant will be assessed with Trauma Symptom Checklist 40 to evaluate trauma intensity. Moreover, subjects who had developed PTG or did not have any trauma intensity will be excluded from the study. Blinded treatment will be provided to subjects meeting eligibility criteria and will be randomized into two groups sequentially as they agree to participate. The nature-based walk will be used as an intervention or experimental group vs the control (sit in nature). The study outcomes will be observed at baseline and 3-month follow-up. Discussion: This trial will provide information on the effectiveness of nature-based walk therapy. Moreover, one of the more promising findings of this research will be essential information about trauma-related psychophysiological effects. This study will also evaluate both (experimental and control) groups that influence whether negative changes accompany positive changes in the aftermath of trauma or not. Trial registration: The trial was registered with ClinicalTrials.gov (NCT04592770).